Pelatihan Penggunaan Media Alat Peraga Pendidikan di era Industri 4.0 pada SMK Sulawesi Barat - Wahyudi; Amiruddin; Wirawan Setialaksana; Akmal Hidayat; Kurnia Prima Putra; Fadhlirrahman Baso; Israwati Hamsar (Jurusan Teknik Informatika dan Komputer, 2023)
This training program aims to improve the competence of vocational high school (SMK) teachers in Polman District, West Sulawesi Province, in using educational aids as a learning medium in the era of industry 4.0, in order to enhance the learning outcomes of students in SMK Negeri Sulawesi Barat. The activity is conducted in the form of training on the use of educational aids as a learning medium for SMK teachers. The participants of this training program consist of 30 teachers from SMK Negeri Paku Polewali Mandar Sulawei Barat. Based on the results obtained, this community service activity has been successfully implemented in accordance with the expectations of the service team and participants. The percentage of achievement of the community service activity over 2 days is 93.25%.